(3eQhL GdPgH heYGOf GdLhgQs - (3Ydj Hf GdMSjf Hf Ydj, CHh GdMSf GdeSYhOj,J (B346 (3g` s
(3ChdgG (B:s
(3PcQ edhc GdWhGFa bGd GdeSYhOi QMeI Gddg (B: (3hJfGRY GdfGS ai edhc GdWhGFa GdaQS cGfhG Ch ef GdfHjW Ch ef GdYQH s
(3BNQgG (B:s
(3jfJgi HPcQ GdHhGOi ef GdYQH BNQ GdeLdO GdKGfi hjJdhg ai GdLRA GdKGdK (B: (3PcQ OjGfGJ GdYQH hBQGFgG ai GdLGgdjI hJaQbgG ai GdHdGO s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B277s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs